Pengaruh Cara Pengolahan terhadapMutu Bakteriologis Ikan Tongkol (Euthynnus affinis) Pindang Siap Santap - Ekawati Purwijantiningsih Exsyupransia Mursyanti (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The objectiveof this present research was toknowthe influence ofvarious way ofcooking on bacteriologicalquality of ready-to-eat salted little tunafish (Euthynnusaffinis).Previousstudyhas shown thatbacteriological quality ofsaltedtunafishfrom markets in Yogyakarta were not fulfill the requirements based on SNI 01-2717-1992. It was shown that the aerobic plate countswere high, i.e.2.4 x 105– 5.27 x 107CFU/g. Coliformcountranged from < 2.5 x 101- > 6.5 x 106CFU/g.Fromthe20samples observed, only 1 sample did not contain V. parahaemolyticus and 4 samples were negative from Salmonella. Therefore,it needs to bestudied whether thevarious way ofcookingsuch asfrying, fryingwith flour, fryingwith egg and fryingwith chili sauce were effectivein removing any of the groups of bacteria examined from saltedlittle tuna fish  sample. The bacterial groups examined as indicator  of quality were Staphylococcus aureus, Coliform, Salmonellaand Vibrio parahaemolyticus. The aerobic plate counts were also taken. The result showed that the various way of cooking wereeffective in reducing the aerobic plate counts, S. aureusand Coliform. Frying with chili sauce was the best cookingprocedure because it can reduced the highest number of aerobic plate counts, S.aureusand Coliform. Salmonellaand V. parahaemolyticuswere not detected in all cooking samples.